Analisis Studi Hubungan Parasosial dengan Kasus Seunghan dan Penggemar RIIZE di Indonesia - Nurfadhilah, Riani Amalia; Koesanto, Stefani Made Ayu Artharini (Universitas Terbuka, 2025)
The advancement of technology and mass media has had a significant impact on the formation of parasocial relationships between fans and their idols, particularly in the growing phenomenon of K-Pop. This study aims to analyze how the use of social media by RIIZE fans relates to the situation experienced by Seunghan. Using a netnographic approach, this research observes fan interactions on platform X from October 11 to November 1, 2024. The results show that RIIZE fans expressed support, protests, and emotional reactions toward SM Entertainment's decision regarding Seunghan's departure from the group. Fans demonstrated high loyalty through support movements and solidarity, while also criticizing the agency's decision, which was perceived as unjust. This study reveals that parasocial relationships can influence fan behavior in voicing opinions and shaping public narratives about their idols. Social media serves as a space for fans to advocate for their idols' rights and create a broader social impact within the fan community